2010
DOI: 10.1128/mcb.00601-10
|View full text |Cite|
|
Sign up to set email alerts
|

Unbiased, Genome-Wide In Vivo Mapping of Transcriptional Regulatory Elements Reveals Sex Differences in Chromatin Structure Associated with Sex-Specific Liver Gene Expression

Abstract: We have used a simple and efficient method to identify condition-specific transcriptional regulatory sites in vivo to help elucidate the molecular basis of sex-related differences in transcription, which are widespread in mammalian tissues and affect normal physiology, drug response, inflammation, and disease. To systematically uncover transcriptional regulators responsible for these differences, we used DNase hypersensitivity analysis coupled with high-throughput sequencing to produce condition-specific maps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
133
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(137 citation statements)
references
References 62 publications
(101 reference statements)
3
133
1
Order By: Relevance
“…SGTB expression did not correlate with age, metastasis, tumor size, cirrhosis, the level of AFP, but notably correlated with gender, histological grade (P<0.001) and HBsAg (P=0.002) ( Table 1). Although the sgtb gene is considered as weakly female specific in mouse liver in some research [14], we haven't find the discrepancy between the male and female human paracancerous liver tissues.…”
Section: Resultscontrasting
confidence: 58%
“…SGTB expression did not correlate with age, metastasis, tumor size, cirrhosis, the level of AFP, but notably correlated with gender, histological grade (P<0.001) and HBsAg (P=0.002) ( Table 1). Although the sgtb gene is considered as weakly female specific in mouse liver in some research [14], we haven't find the discrepancy between the male and female human paracancerous liver tissues.…”
Section: Resultscontrasting
confidence: 58%
“…Damage-induced chromatin changes were dampened in both the expansion and compaction phases after overexpression of the Set1/Ash2 methyltransferase ASH2L (Fig. 1B), which globally increases the H3 lysine 4 methyl mark that is implicated in transcriptional activation and mediates chromatin expansion through recruitment of chromatin modifiers (Boyle et al, 2008; Chambeyron and Bickmore, 2004; Consortium et al, 2007; Ling et al, 2010; Luco et al, 2010; Santos-Rosa et al, 2002; Shimada et al, 2006). In agreement with recent findings (Khurana et al, 2014) we conclude that the DNA damage response involves initial expansion of chromatin followed by a phase of chromatin condensation.…”
Section: Resultsmentioning
confidence: 99%
“…The enrichment of sex-specific lincRNAs for nearby and correspondingly sex-biased binding by GH-dependent transcriptional activators and the inverse pattern of sex-biased binding by GH-dependent repressors indicate a role for these TFs in the proximal regulation of sex-specific lincRNA transcription, in addition to their established roles in regulating expression of sex-specific protein-coding genes (52)(53)(54)(55). One such GH-regulated TF, STAT5, is a key GH-responsive factor whose deletion in male mouse liver leads to widespread disruption of sex-specific coding-gene expression (57) and sex-specific lincRNA expression ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated whether sex-specific lincRNA genes are enriched for nearby sites of sex-dependent chromatin accessibility, which bind TFs in a sex-dependent manner (54)(55)(56) and can be detected as sex-biased DHS (52). We found that the stringent (i.e., GH-regulated) male-specific lincRNAs are significantly enriched for nearby (within 10 kb) male-biased DHS (P ϭ 5.77eϪ11) and depleted of female-biased DHS.…”
Section: Identification Of Liver-expressed Lincrnasmentioning
confidence: 98%
See 1 more Smart Citation